2020
DOI: 10.1136/bmj.m3840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of monitoring surgical outcomes using control charts to reduce major adverse events in patients: cluster randomised trial

Abstract: ObjectiveTo determine the effect of introducing prospective monitoring of outcomes using control charts and regular feedback on indicators to surgical teams on major adverse events in patients.DesignNational, parallel, cluster randomised trial embedding a difference-in-differences analysis.Setting40 surgical departments of hospitals across France.Participants155 362 adults who underwent digestive tract surgery. 20 of the surgical departments were randomised to prospective monitoring of outcomes using control c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 38 publications
(72 reference statements)
0
49
0
Order By: Relevance
“…Quality indicators (QIs) have been increasingly used as a mechanism to measure broad aspects of care, 9 identify unwanted variation 10 11 and drive quality improvement. 12 For AMI, a suite of QIs exist which are valid, 13 internationally recognised 14 and have built on earlier indicators that have an inverse association with mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Quality indicators (QIs) have been increasingly used as a mechanism to measure broad aspects of care, 9 identify unwanted variation 10 11 and drive quality improvement. 12 For AMI, a suite of QIs exist which are valid, 13 internationally recognised 14 and have built on earlier indicators that have an inverse association with mortality.…”
Section: Introductionmentioning
confidence: 99%
“… 18 Feedback on patient outcomes can reduce major adverse events following surgery. 19 Although these studies from well resourced environments provide support for the trial hypothesis, the ASOS-2 intervention did not decrease postoperative mortality in a low-resource environment.…”
Section: Discussionmentioning
confidence: 82%
“…Literature shows that resistance among the professionals may exist for implementing scorecards or surgeon outcomes. 17 20 We did not experience any resistance and were, in fact, encouraged by our surgical staff. The intention was to install feedback loops without being judgmental.…”
Section: Discussionmentioning
confidence: 99%
“… 19 A French study on a nationwide scale demonstrated a positive correlation with the outcome of care after implementing control cards. 20 Our future goals will be to implement the new International Consortium for Health Outcomes Measurement (ICHOM) set for hand wrist disorders 28 (see Fig. 9 ), improve dashboards for patients, surgeons, and therapists.…”
Section: Discussionmentioning
confidence: 99%